Digital Transformation and Institutional Governance in Sharia Investment Markets: A Computational Perspective on Emerging Financial Ecosystems - Firmaningtyas, Renovalia Satya; Apriantoro, Muhamad Subhi (TAWAZUN: Journal of Sharia Economic Law, 2026)
The rapid growth of the Islamic finance industry and the increasing use of digital platforms have encouraged the emergence of virtual academic events discussing Sharia investment. Webinars, online seminars, and panel discussions generate large volumes of unstructured digital data that can serve as valuable sources for understanding contemporary Sharia investment discourse. However, the utilization of such data in academic research remains limited. Therefore, this study aims to analyze the discourse on Sharia investment emerging from virtual academic events through a netnographic approach. The study employs netnography supported by text mining techniques to explore dominant themes and discussion patterns related to Sharia investment in digital environments. Data were purposively collected from six virtual academic events conducted between 2020 and 2025, involving nine Sharia investment experts from five countries. The dataset consists of 23,386 words obtained through automated speech-to-text transcription and manually verified for accuracy. The findings reveal that Sharia compliance, investment governance, business ethics, and digitalization are the dominant themes, reflecting the growing relevance of Sharia investment in the digital era.